2012
DOI: 10.1088/1748-9326/7/1/015505
|View full text |Cite
|
Sign up to set email alerts
|

Do limiting factors at Alaskan treelines shift with climatic regimes?

Abstract: Trees at Alaskan treelines are assumed to be limited by temperature and to expand upslope and/or to higher latitudes with global warming. However, recent studies describe negative temperature responses and drought stress of Alaskan treeline trees in recent decades. In this study, we have analyzed the responses of treeline white spruce to temperature and precipitation according to different climatic regimes in Alaska, described as negative (cool) and positive (warm) phases of the Pacific Decadal Oscillation (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 54 publications
3
57
0
Order By: Relevance
“…Drought stress as a local factor impeding tree growth in recent decades has been supposed for different treeline environments (e.g. Lloyd and Fastie, 2002;Daniels and Veblen, 2004;Dulamsuren et al, 2010;Zhang et al, 2011;Fajardo and McIntire, 2012;Ohse et al, 2012).…”
Section: Tree Physiognomy and Growth Patternsmentioning
confidence: 99%
“…Drought stress as a local factor impeding tree growth in recent decades has been supposed for different treeline environments (e.g. Lloyd and Fastie, 2002;Daniels and Veblen, 2004;Dulamsuren et al, 2010;Zhang et al, 2011;Fajardo and McIntire, 2012;Ohse et al, 2012).…”
Section: Tree Physiognomy and Growth Patternsmentioning
confidence: 99%
“…Several studies have shown temperature increases during the latter half of the 20 th century have limited, rather than facilitated, radial growth of white spruce (Barber et al 2000;Davi et al 2003;D' Arrigo et al 2004D' Arrigo et al , 2007Wilmking et al 2004;Wilmking and Juday 2005), although this response also varies regionally and among sites (Ohse et al 2012). Dif- ferential effects seem to relate to the relative change in precipitation versus temperature with the phase change in the PDO.…”
Section: Pdo Phases and Factors Limiting White Spruce Growthmentioning
confidence: 99%
“…These findings are consistent with other studies conducted on interior white spruce forests growing in the rain shadows of mountain ranges. At moisture-limited sites, warm temperatures limit white spruce growth (Barber et al 2000, Lloyd andFastie 2002), even at altitudinal treeline (Lloyd and Fastie 2002, Youngblut and Luckman 2008, Ohse et al 2012.…”
Section: Pdo Phases and Factors Limiting White Spruce Growthmentioning
confidence: 99%
See 2 more Smart Citations